Development of Podcast Media Based on the Spotify Application in History Learning on the Influence of Islamic Religion and Culture in Indonesia at Profession Bina Vocational School - Suroyo; Adellia, Putri; Isjoni Ishaq (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
Education is an effort to become an active individual in developing the potential that exists within him. In developing personal potential, every individual needs to be guided and facilitated in carrying out learning activities. Learning media is one component of the teaching and learning process that has an important role in supporting the success of the teaching and learning process in the classroom. Considering the importance of technology in the 21st century, researchers are interested in developing learning media as a tool in the learning process, namely podcast media based on the Spotify application. This research aims to develop podcast media based on the Spotify application on the influence of Islamic religion and culture in Indonesia. This type of research is development research with a 4D development model, namely define, design, develop, and disseminate. The results of expert validation for podcast media based on the Spotify application from material experts were 94%,%, % from media experts 90%, % from small group assessments 92.1% and 90.1% from large group trials with the overall category